Penegakan Hukum Terhadap Pelaku Tindak Pidana Illegal Fishing Di Wilayah Kerja Kejaksaan Negeri Serdang Bedagai - Fauzan Irgi Hasibuan (Iuris Studia: Jurnal Kajian Hukum, 2021)
The sovereignty of a country in the sea is very dependent on the ability of the state to physically prevent the sea area it controls. The wider the sea area controlled by a country, the greater the responsibility of the state to oversee it. Indonesia has stated that it will assume responsibility for the prevention of this vast sea area, which has an area of 5.8 million square kilometers, of which 60% of the area is a marine area under the sovereignty of the Republic of Indonesia. Indonesian territorial waters, especially border areas, need to be managed properly for the utilization of natural resources in the vicinity so that they can be used for the welfare of the people. There are many problems faced by the Indonesian government in managing the territorial waters of the country, one of which is Illegal, Unreported, and Unregulated Fishing (IUU Fishing) or what we usually know as illegal fishing. Illegal fishing has caused multidimensional impacts related to economic, social, cultural and environmental aspects. This is a logical consequence of the function of the sea as an ecosystem in which it contains three basic functions, namely yield (production), environmental and social. This type of research is a normative juridical research. How are the legal provisions governing the criminal act of illegal fishing, how is the law enforcement process against illegal fishing, and what are the obstacles in the law enforcement process and what are the solutions or efforts that should be made so that the law enforcement process against illegal crimes fishing can be carried out properly. The legal provisions regarding the criminal act of illegal fishing are contained in Article 1 point 5 of Law Number 45 of 2009 concerning Amendments to Law Number 31 of 2004 concerning Fisheries, fishing is an activity that obtains fish in waters that are not in a state of being cultivated with tools or equipment. in any way, including activities that use ships to load, transport, store, cool, handle, process, and/or preserve them. Law enforcement is an effort made so that the law can function and run properly and is obeyed by everyone. Law enforcement in a narrow sense is carried out by the Police, Prosecutors, Courts and Correctional Institutions